Expert Evidence and Competence Standards in Indonesian Criminal Procedure: Revisiting KUHAP, the Draft KUHAP, and Law No. 2 of 2017 - M. Rochman (JURNAL AKTA, 2025)
The role of experts in the criminal justice system constitutes an important instrument for ensuring objectivity in the evidentiary process; however, regulatory ambiguities remain concerning the limits of expert authority, certification requirements, regulatory synchronization, and legal protection within the Criminal Procedure Code, the Draft Criminal Procedure Code, and Law Number 2 of 2017 on Construction Services. This study aims to examine the position and role of experts in Indonesian criminal law based on these regulations in order to provide greater legal certainty and enhanced protection for expert witnesses. The research employs a normative juridical method using statutory and comparative approaches. The findings reveal persistent ambiguities across the examined regulations, including the absence of clear provisions defining the scope of expert authority in criminal proceedings, uncertainty regarding the function of experts in providing technical recommendations, unclear requirements for special certification particularly in cases where experts possess practical expertise without formal certification the lack of synchronization between KUHAP, RUU-KUHAP, and the Construction Services Law. The study underscores the need for clearer, harmonized regulations governing expert testimony to ensure legal certainty, professional accountability, and effective protection for experts within Indonesia’s criminal justice system.